Identification of an Agrobacterium tumefaciens virulence gene inducer from the pinaceous gymnosperm Pseudotsuga menziesii. - Morris, J W (1990)
Inducible T-strand mobilization from the Ti plasmid of Agrobacterium tumefaciens to the genome of a plant host is mediated by the activation of a cascade of bacterial virulence genes. It is initiated when the bacterium senses the presence of a low molecular weight inducer secreted by the plant. Although many hydroxyphenylpropanoid and phenolic compounds can activate the virulence cascade, the only native inducers that have been identified to date are acetosyringone and hydroxyacetosyringone. A new inducer, the phenylpropanoid glucoside coniferin, has now been isolated from Pseudotsuga menziesii (Douglas-fir). Agrobacterium strains that were more tumorigenic on gymnosperms were more effectively induced by coniferin.